Introduction to Dissection, V2.0 (Out of Print) - Lawrence Wineski; Perry Riggins; Rebecca Sealand; Christopher May (Association of American Medical Colleges, 2007)
Abstract Many health science students do not enroll in undergraduate dissection-based anatomy courses during their preprofessional education. As a result, they are not familiar with dissection instruments and the mechanics of dissection, and are poorly prepared for medical anatomy courses. This program is designed to help overcome those deficits. It serves as an introduction to dissection in a human gross anatomy course for first-year medical students. It can be used either as a component of a structured classroom session or independently by individual students. The content is presented in a series of video clips arranged in two sections, each containing multiple chapters. The program is menu-driven, allowing viewing of the entire content in sequence or selected chapters in any order. Students at Morehouse School of Medicine use this program independently before beginning dissection. Students report (both informally and via on-line survey) that they have a better understanding of what they are shopping for when they purchase their dissecting instruments after viewing the program. Also, they are pleased with the utility of the instruments during the course of the dissections. Both faculty and students report that students are more comfortable and confident while conducting their first dissection after viewing the program. Dissection faculty believe the first dissection lab proceeds more efficiently since after implementing this resource. Therefore, this program has helped the students work more independently and effectively in human gross anatomy.